Singular representation - Openshaw, J (2018)
This thesis is a study of aboutness. It defends the claim that we have singular thoughts about ordinary objects and argues that an essential part of how we do so is by maintaining singular representations. This proposal allows us to avoid traditional, unsatisfying conceptions of the scope of singular thought while restoring the sense in which such thought is a distinctively epistemic achievement. Reconnecting the study of aboutness with epistemology promises to alleviate the sense of directionlessness in the contemporary literature, offering a firmer grip on the phenomenon along with new, systematic resources for its investigation. Chapters 1–2 explore the effects of contextualist machinery on orthodox views about singular thought. It is widely thought that if there is to be a plausible connection between the truth of a de re attitude report about a subject and that subject’s possession of a singular thought, then there can be no acquaintance requirement(s) on singular thought. Chapter 1 shows that this view rests on a faulty picture of how we talk about attitudes. Indeed, the truth of a de re attitude report cannot be taken to track the singular/non-singular distinction without collapsing it. A new, contextualist picture is needed. That there must be a distinction between singular and non-singular intentionality is emphasized in Chapter 2, where a key explanatory role for singular thought—brought out by a thought experiment due to Strawson—is examined. I show that the role does not call for any distinctive kind of mental content. Once we abandon the two widespread views questioned in Chapters 1–2, our grip on the phenomenon of singular aboutness is loosened: it is not constitutively tied to the kinds of attitude-reporting data or mental content by which it is often assumed to be revealed. Where are we to look for insight? What makes something the object of a singular thought? According to Russell, it is a datum of intuition that singular thought involves a kind of knowledge; a theory of aboutness will precisify the intuitive notion of ‘knowing which thing one is thinking about’ in order to capture this demand in a philosophically revealing way. If Russell is right, teasing out this connection to knowledge will allow us to see what it takes for a particular thing to be the immediate subject matter of thought. Chapter 3 discusses Evans’s theory of this kind. Chapter 4 examines recent work by Dickie. While serious concerns emerge in each case, insights recovered are used to precisify Russell’s requirement, leading to a novel picture of singular representation and the epistemic character of this achievement. While the chapters follow a narrative, providing an extended rationale for the proposal in Chapter 4, each may be read in isolation by those familiar with the philosophical issues. For those who are not, the Introduction provides sufficient background.